Final Report - Bodnar, R. J. (Virginia Tech, Blacksburg, VA, 2005)
The aim of this project was to determine phase equilibrium and PVT properties of fluids in the water-methane system using synthetic fluid inclusions. This information is critical to understanding the behavior of natural fluid inclusions trapped in hydrocarbon-bearing environments such as sedimentary basins, oil and gas fields, methane hydrate occurrences and Mississippi Valley type Pb-Zn deposits.